2022
DOI: 10.3390/polym14091658
|View full text |Cite
|
Sign up to set email alerts
|

Improving Electromagnetic Interference Shielding While Retaining Mechanical Properties of Carbon Fiber-Based Composites by Introducing Carbon Nanofiber Sheet into Laminate Structure

Abstract: The demands for carbon fiber reinforced composites (CFRCs) are growing in the aviation industry for fuel consumption savings, despite the increasing risk of electromagnetic interference (EMI). In this work, polyacrylonitrile (PAN) sheets were prepared by electrospinning. Carbon nanofiber (CNF) sheets were obtained by the carbonization of PAN sheets. The laminate structures of the CF reinforced bismaleimide (BMI)-based composites were specially designed by introducing two thin CNF sheets in the upper and bottom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Chen et al 27 added different concentrations of CNTs into PAN spinning solution and measured the SE of CNT/PAN NFMs after carbonization. Additionally, Ma et al 28 introduced carbonized PAN nanofibers into the aerospace materials, and the results showed that the existence of carbon nanofibers enhanced the EMI shielding property of the materials by 35%.…”
Section: Electrospun Nfms For Electromagnetic Shieldingmentioning
confidence: 99%
“…Chen et al 27 added different concentrations of CNTs into PAN spinning solution and measured the SE of CNT/PAN NFMs after carbonization. Additionally, Ma et al 28 introduced carbonized PAN nanofibers into the aerospace materials, and the results showed that the existence of carbon nanofibers enhanced the EMI shielding property of the materials by 35%.…”
Section: Electrospun Nfms For Electromagnetic Shieldingmentioning
confidence: 99%
“…Xu et al 115 prepared high‐performance copolymerized PAN (coPAN) nanofibers using copolymerization and electrospinning techniques, increasing tensile strength from 304 to 595 MPa. Subsequently, Ma et al 116 obtained CNF by high‐temperature carbonization of PAN and introduced it into the upper and lower layers of carbon fiber reinforced composites (CFRCs). Incorporating CNF does not affect the composite material's interlaminar shear strength (ILSS) and significantly improves its shielding performance by 35%.…”
Section: Electrospun Emi Shielding Dopantsmentioning
confidence: 99%
“…imparts EMI shielding performance to them. Different types of fillers based on carbon (carbon black, carbon fibers, carbon nanotubes, graphite, or graphene), as well as inorganic fillers (metals, metal oxides, MXenes, ferrites), have been tested for this purpose [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Although the rubber matrix is the carrier of the main characteristics, the type and the content of the filler can have significant influences on process-ability, physical–mechanical or dynamic properties, and EMI shielding performance.…”
Section: Introductionmentioning
confidence: 99%